(untitled) (Medico Legal Update, 2019)
Background: There is a need to understand the concepts especially like court room procedures among the medical students as the practical experience is encountered in many medico legal cases in future as doctors. Creating an educational instructive video for promotion of understanding the concepts of forensic medicine among all budding doctors in their curriculum. Aim and Objectives: To study the utility and assess of role play using videos in improving the knowledge and attitude of students regarding courtroom procedures in an Indian court. Methodology: A descriptive questionnaire based study survey was done after obtaining informed consent from students. The pretest and posttest were randomized by giving a number to the students and also to avoid inter participation bias. Validation of questionnaire was then done. The video on court room procedure was done and validated with the help of forensic experts and lawyer colleagues. Statistical and comparison analysis was done. Results: The present study about 222 second year medical students were assessed, the study showed gender and varied age distribution between 18 to 23 years. The study showed various aspects of knowledge and attitude. In knowledge component, some of the questions posed required a definitive positive or negative response. In the knowledge component, out of the total 28 questions posed, 22 questions showed highly significant changes [p < 0.5 significance] in the questionnaire results. In the attitude component about how a doctor behaves inside the court room, of the total 16 questions posed, 10 questions showed highly significant changes[ p< 0.5 significance] in the questionnaire results.The study also showed various responses regarding the video and positively revealed that such an educational tool is needed and would definitely make a change in curriculum.